De la mano de Dios. El nacionalismo católico chileno y la Guerra del Pacífico, 1879-1881 - McEvoy, Carmen (Pontificia Universidad Católica del Perú. Fondo Editorial, 2004)
This article analyzes the role played by the Catholic Church’s intellectual elite in the construction of a nationalistic discourse during the War of the Pacific, 1879-1884. This nationalistic rhetoric, which served the interests of the Chilean state, purified the conflict of its political and economic connotations, and conferred upon it a sacred and eternal justification. Cultural agents, through the carefully calculated use of the means of communication, converted the idea that Divine Providence supported the Chilean cause into a driving force. By means of its participation in this ideological debate and by mobilizing civil society, the Chilean church probably aimed to defend its preeminent role as the main cultural frame of reference in the face of the threat posed by other social actors which disputed its hegemony during that period.

Los círculos intelectuales de la Iglesia católica jugaron un papel fundamental en la elaboración de un discurso nacionalista, funcional a los intereses del Estado chileno. Mediante tal discurso, el conflicto bélico fue librado de sus impurezas materiales y asumió una justificación eterna y sagrada. El apoyo de la Divina Providencia hacia la causa de Chile fue una de las ideas-fuerza cuyos productores culturales desarrollaron ante la opinión pública a través de un hábil manejo de los medios de comunicación. Con su participación en el debate ideológico y en la movilización de la sociedad civil, que ocurrió como consecuencia de la guerra, la Iglesia chilena habría intentado defender su preeminencia como referente cultural ante la amenaza de otros actores sociales que, por esos años, le estaban disputando su hegemonía.
Keywords: Historia; Guerra del Pacífico; https://purl.org/pe-repo/ocde/ford#6.01.01